The Role of Grammar Awareness in Students’ Writing Performance - Anugrah Puspita Ayu Muhammad; Asna Wirayanti; Waode Ade Sarasmita Uke (PT. Global Research Collaboration, 2025)
This study investigates the role of grammar awareness in students’ writing performance among English Department students. The research aims to explore how students’ awareness and understanding of grammatical structures contribute to the accuracy, coherence, and overall quality of their writing. The study employed a quantitative descriptive method with a correlational design. Data were collected from 40 English Department students through a grammar awareness questionnaire and written essay assessments. The data were analyzed using descriptive statistics and Pearson correlation analysis to examine the relationship between grammar awareness and writing performance. The findings revealed a significant positive correlation between students’ grammar awareness and their writing performance, indicating that students with higher grammatical awareness tend to produce more accurate and cohesive written texts. The results suggest that explicit grammar awareness instruction should be integrated into writing courses to enhance students’ linguistic competence and writing quality. This study highlights the importance of raising students’ awareness of grammar not only as a set of rules but also as a tool for effective communication in academic writing contexts.